Familial brucellosis osteoarthritis: A report of two patients - Qi Huang; Xin Liao (IDCases, 2023)
Brucellosis is a zoonotic infectious disease caused by brucella infection, which is a natural epidemic disease that infects humans and animals such as cattle, sheep, pigs, and dogs. Clinically, it is mainly manifested as fever, excessive sweating, joint pain and swollen liver, spleen and lymph nodes of different diseases. We report two cases of brucellosis in a family living in China. They both developed brucellosis osteoarthritis, with a 39-year-old man in the left elbow and a 68-year-old woman presenting with brucellosis spondylitis. They were well treated with doxycycline and rifampicin. Investigating a common source found that the family raised goats.